Reimagining justice in contexts of transition - (:unkn) unknown (My University, 2013)
Panel Courts and politics: dynamics and challenges for the effectiveness and legitimacy of Africa's judiciaries, mod. Alexander Stroh et Charlotte Heyl http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=1773
Keywords: African Research